An Investigation Into The Impact Of Psychic Distance On The Performance Of International Hypermarkets In Malaysia - Oyekan, Umar Ajibade (2003)
Research into firm internationalisation has identified psychic distance as a key factor in explaining variations in both expansion patterns and organisational performance. Despite the substantial growth in research on the internationalisation of retailing, most contributions have been highly descriptive and generally bereft of coherent theoretical frameworks. This paper sets out to retest (with some critical adjustments) the theoretical framework and arguments presented by Evans et al (2000) and Evans and Mavondo (2002). The paper also investigates the impact of the new regulations for hypermarkets in Malaysia on firm performance. The results of the study show that psychic distance has a significant impact on the activities of hypermarkets in Malaysia. The results show support for a psychic distance paradox, and also highlight many other pertinent issues that are relevant for firms in the Malaysian hypermarket sector.